Kebijakan Rendah Emisi Negara Anggota G20 dan Kinerja Ekspor Kendaraan Bermotor Indonesia: IPB University - Alqodri, Muhammad Iqbal; Widyastutik (IPB University, 2023)
Indonesia is one of the world's motor vehicle exporters, ranking 14th globally, 11th in the G20, and 2nd in ASEAN. The increasing emissions from the transportation sector have prompted the G20 countries to implement a low-emission policy through an electric vehicle policy. Concerns arose over the decline in Indonesia's exports of oil-fueled motor vehicles to G20 member countries. This study aims to analyze differences in the performance of Indonesia's motor vehicle exports when the EVP policy was implemented in 11 G20 member countries in 2012-2021. RCA, EPD, X-Model, and panel data regression are the research methods used. Results of RCA analysis show that Indonesia has comparative competitiveness with Mexico, Saudi Arabia, and South Africa. Regarding EPD and X-Model, Indonesian motor vehicle products are in a falling star position with less potential market development. Panel data regression analysis shows that the variable GDP per capita of the destination country, Indonesia's dummy EVP, destination country's dummy EVP is positive and significant. Meanwhile, the economic distance variable has a negative and significant effect, but the real exchange rate, import tariffs, and dummy Covid-19 variables are not significant. Policy recommendations from analysis findings in the form of market intelligence, production incentives, purchase incentives, to the implementation of the Mutual Recognition Arrangement (MRA) scheme.